Studi Tentang Pendidikan Anak Dalam Keluarga Persfektif Islam Di Provinsi Lampung - Nurdiana Sari (Jurnal Dewantara, 2020)
The explanation of the education of children in the family with an Islamic perspective in Lampung Province, several conclusions can be drawn that education in the family with an Islamic perspective is education based on Islamic religious guidance which is applied in the family which is intended to shape children to become human beings who believe and fear God. The Almighty, and has noble character which includes ethics, morals, character, spirituality or understanding and experience of religious values ​​in everyday life. Islamic religious education for children must be carried out since the fetus is still in the womb. This Islamic religious education is carried out by holding prayers and reading the Quran. When the baby is born, it should be continued with the next Islamic religious education, namely listening to the call to prayer and iqamah, giving a good name, walimatul aqiqah and walimatul circumcision. Patterns of Islamic education that can be practiced by parents are exemplary patterns, customs, advice, attention and patterns of rewards and punishments. The patterns of education that are practiced do not stand alone, but support each other and are related to one another. These patterns are also practiced according to the existing situation and conditions.